PROBLEMATIKA INDEPENDENSI KOMISI KEBENARAN DAN REKONSILIASI ACEH - Pasha, Zahlul (Penerbit Universitas Atma Jaya Yogyakarta, 2017)
ABSTRACTAfter signing the MoU between the Indonesian government and the Free Aceh Movement, a lot of interesting dynamics going on in Aceh, which is the Qanun KKR Aceh. As an independent agency, the Aceh TRC duty to disclose the truth on the alleged past human rights violations in Aceh. This paper examines the nature of the independence of Aceh TRC is based on theoretical characteristics of an independent institution. Based on the results of the study found that the Aceh TRC has a number of independent properties include: an odd number of members, the independent election commission members, the election and dismissal of members of the commission are closely regulated and has the authority to regulate themselves (self-regulated bodies). However, on the other hand also found two other things that escape is set regarding the nature of the independence of Aceh TRC is concerning institutional decision-making procedures and functions of the commission as well as regarding filling positions that are not members of the commission be gradual (staggered terms) but simultaneously.Â Keywords: Independency, Komisi Kebenaran dan Rekonsiliasi Aceh.Â INTISARIPasca penandatanganan MoU Helsinki antara Pemerintah Indonesia dengan GerakanAceh Merdeka, banyak dinamika menarik yang terjadi di Aceh, salah satunyaadalah pengesahan Qanun KKR Aceh. Sebagai lembaga independen, KKR Aceh bertugas mengungkap kebenaran atas dugaan pelanggaran HAM berat masa lalu di Aceh. Tulisan ini berusaha mengkaji sifat independensi KKR Aceh berdasarkan ciri teroritik suatu lembaga independen. Berdasarkan hasil kajian ditemukan bahwa KKR Aceh memiliki sejumlah sifat independenmeliputi: jumlah anggota yang ganjil, proses pemilihan anggota komisi yang independen, pemilihan dan pemberhentian anggota komisi diatur jelas serta memiliki kewenangan untuk mengatur dirinya sendiri (self regulated bodies). Namun, di sisi lain juga ditemukan dua hal lain yang luput diatur berkenaan sifat independensi KKR Aceh, yaitu menyangkut prosedur pengambilan keputusan kelembagaan dan fungsi komisi serta perihal pengisian jabatan anggota komisi yang tidak dilakukan secara bertahap(staggered terms) melainkan bersamaan.Â Kata Kunci: Independensi, Komisi Kebenaran dan Rekonsiliasi Aceh.